A Computing Method to Determine the Performance of an Ionic Liquid Gel Soft Actuator. (2nd May 2018) - He, Bin; Zhang, Chenghong; Zhou, Yanmin; Wang, Zhipeng
Abstract : A new type of soft actuator material—an ionic liquid gel (ILG) that consists of BMIMBF4, HEMA, DEAP, and ZrO2 —is polymerized into a gel state under ultraviolet (UV) light irradiation. In this paper, we first propose that the ILG conforms to the assumptions of hyperelastic theory and that the Mooney-Rivlin model can be used to study the properties of the ILG. Under the five-parameter and nine-parameter Mooney-Rivlin models, the formulas for the calculation of the uniaxial tensile stress, plane uniform tensile stress, and 3D directional stress are deduced. The five-parameter and nine-parameter Mooney-Rivlin models of the ILG with a ZrO2 content of 3 wt% were obtained by uniaxial tensile testing, and the parameters are denoted as c 10, c 01, c 20, c 11, and c 02 and c 10, c 01, c 20, c 11, c 02, c 30, c 21, c 12, and c 03, respectively. Through the analysis and comparison of the uniaxial tensile stress between the calculated and experimental data, the error between the stress data calculated from the five-parameter Mooney-Rivlin model and the experimental data is less than 0.51%, and the error between the stress data calculated from the nine-parameter Mooney-Rivlin model and the experimental data is no more than 8.87%. Hence, our work presents a feasible and credible formula for the calculation of the stress of the ILG. This work opens a new path to assess the performance of a soft actuator composed of an ILG and will contribute to the optimized design of soft robots.